2008
DOI: 10.1016/j.neuroscience.2007.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Neuroretinal xenotransplantation to immunocompetent hosts in a discordant species combination

Abstract: In spite of its immune privileged state, xenotransplantation within the CNS is associated with rapid graft destruction in immunocompetent hosts. Efforts to enhance graft survival have mostly focused on host immune response, whereas relatively little attention has been paid to donor tissue characteristics. In the present paper, we explore long-term survival of xenogeneic full-thickness neuroretinal transplants in immunocompetent hosts and investigate the significance of tissue integrity in relation to graft sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…If we add to this the possibility of enhanced exposure of conventional transplantation and retina-restricted antigens in fragmented donor tissue, acute rejection of such grafts is hardly surprising [6]. In accordance with our earlier reports on transplantation to the SRS [11,16], donor tissue integrity appears to be an important factor for survival of neuroretinal grafts also in non-immune privileged sites.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…If we add to this the possibility of enhanced exposure of conventional transplantation and retina-restricted antigens in fragmented donor tissue, acute rejection of such grafts is hardly surprising [6]. In accordance with our earlier reports on transplantation to the SRS [11,16], donor tissue integrity appears to be an important factor for survival of neuroretinal grafts also in non-immune privileged sites.…”
Section: Discussionsupporting
confidence: 79%
“…We have here shown that the fullthickness neuroretina enjoys only partial immune privilege, and that this privilege is related to donor age. These results together with previous findings that neuroretinal immune privilege also depends on donor tissue integrity [11,16], and that the immune privilege of the SRS is most likely not complete [3,28], indicate that any strategy to transplant neuroretina should include efforts to keep the donor tissue intact and to minimize disturbance of the SRS. The fact that survival of neuroretinal grafts is related to donor age, tissue integrity, and the immune-privileged state of the recipient site, these important points may help us avoid unnecessary pitfalls when devising strategies and therapies for curing retinal degenerative disease.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The removal of inner retinal layers to isolate photoreceptors has been attempted for more than 2 decades by enzymatic and mechanical disruption [2,32,35]. However, grafts achieved with these techniques have not yet been shown to achieve robust organization, survival or integration after transplantation, possibly because of pretransplantation cell death, Müller cell trauma and an increased immunogenicity [2,36,37,38,39,40]. To overcome these complications, the isolation of specific cell types and the removal of others by modulating retinal development in vitro may offer a more attractive alternative, since disruption of vital cell-to-cell contacts is avoided [4,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this is the problem of anoikis, an apoptotic cascade initiated by lack of cell anchorage [197,198]. This is supported by the observation that RPE cells transplanted as a whole sheet survive better than as a suspension [199,200]. An additional contributing factor to cell death is the hostility of the micro-environment, which includes the presence of apoptotic signals, inflammatory cells, and damage to the surrounding architecture [146,201,202].…”
Section: Accepted Manuscriptmentioning
confidence: 99%